Potret Islamic Studies dan Islam Apologetics (Telaah atas Pandangan Majid Daneshgar tentang Islamic Apologetics) - Afifah, Tsaqifa Aulya (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
In the academic environment, learning Islamic Studies gives rise to various polemics and debates. This research will discuss the thoughts of contemporary Muslim figure about Islamic Studies, Majid Daneshgar in his book